Structural asymmetries and the health crisis: the imperative of a transformative recovery for the advancement of sustainable development in Latin America and the Caribbean - Alicia Bárcena; Mario Cimoli (CEPAL Review, 2021)
This article underscores the pressing need to transition to a new development model in Latin America and the Caribbean as the region strives to cope with the current health emergency. Statistics show that the Latin American and Caribbean region has been hit harder by the pandemic than any other and that it has also sustained the most damage in economic and social terms. This is attributable to long-standing structural factors that set the stage for the emergence of its present dysfunctional development pattern. The region grew by a scant 0.4% per year between 2014 and 2019 against the backdrop of a widening external productivity gap, deepening structural heterogeneity, low-productivity development paths and a declining share of wages in GDP. All this has eroded its social and economic development process. The economic reactivation effort must therefore be based on a package of coordinated, ambitious structural reforms in the areas of production, fiscal policy and institutional affairs in order to forge an inclusive and sustainable development style.